How perceptions about ease of use and risk explain intention to use mobile payment service in Pakistan? The mediating role of perceived trust - Talat Islam; Saif-Ur-Rehman; Ch. Muhammad Salman Abid; Zeshan Ahmer (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
This research aims to investigate the influence of perceived ease of use and perceived risk on intention to use mobile payment servicesin Pakistan via mediating role of perceived trust. A total of 320 smartphoneusers were approached using a questionnaire-based survey method and hypotheses were tested using hierarchal regression. The results of this study confirm that perception about ease of use and perception about trust of consumers significantly influences the intention to use mobile payment service. Whereas, perceived risk is found insignificant in explaining intention to use mobile payment services in Pakistan but, perception about risk is found as a significant negative influencer of perceived trust among consumers. This study is helpful for mobile payment service providers like Bank's marketing manager, financial institutions, etc. for making their strategies accordingly to tap consumers who prefer traditional cash mode of payment and it is also fruitful for the government and concerned departments to maintain transparency in monetary and economic transactions by m-payment services that can prove a helping hand for developing economies.
Keywords: 330; M-payment; technology adoption; perceived risk; perceived trust; theory of planned behavior; ease of use mobile payment